Caste in India politics - Kothari, Rajni (ed.) (New Delhi Orient Langman, 1970)
A book that studies the confrontation between India$1 (Bs caste system and the Parliamentary form of government in varying contexts and through different methods of investigation.s
Keywords: Indian Politics